IMPLEMENTASI EKONOMI SIRKULAR OLEH SIAM CEMENT GROUP (SCG) DI INDONESIA TAHUN 2022-2024 - Ar-Rahma, Sucia; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Sustainability issues have become a major challenge for developing countries, including Indonesia, in facing global pressure on environmental and economic management. The adoption of the circular economy concept is considered an essential strategy to reduce waste while enhancing resource efficiency This study employs the Pentahelix theory as its analytical, emphasizing collaboration among five key actors government, academia, business, community, and media in supporting the implementation of the circular economy by SCG. The level of analysis focuses on actor groups to understand the patterns of synergy and the respective roles of each party in promoting sustainability. The methodology used is qualitative with a descriptive-explanatory approach, aiming to describe the phenomenon while explaining the interactions among actors in circular economy practices. The research data are derived from primary sources, such as official SCG publications, and secondary sources, including various literatures and supporting reports to strengthen the analysis. The results indicate that SCG’s implementation of the circular economy is realized through waste management programs, the application of Refuse-Derived Fuel (RDF), the reuse of residual materials, the use of renewable energy from biomass, and collaboration with various stakeholders to enhance resource efficiency and reduce waste. These findings show that SCG’s efforts are not solely driven by the company’s internal commitment but are also supported by government initiatives, academic involvement in environmental research, community participation in circular education programs, and the media’s role in raising public awareness. The results demonstrate that the success of SCG’s circular economy implementation is built through cross-sector collaboration that mutually reinforces the development of a sustainable ecosystem in Indonesia. interests, Keywords : Circular Economy, Refuse-Derived Fuel, Waste Management